2005
DOI: 10.1002/ps.1027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraguild predation and lambda‐cyhalothrin on predation efficacy of three acarophagous predators

Abstract: This laboratory study reports the interaction of three predators found in commercial apple orchards in Quebec, Hyaliodes vitripennis (Say) (Hemiptera: Miridae), Harmonia axyridis Pallas (Coleoptera: Coccinellidae) and Amblyseius fallacis (Garman) (Acarina: Phytoseiidae). First, intraguild predation between H vitripennis and the two other predators was characterized in the absence and presence of their extraguild prey, Tetranychus urticae Koch. The results showed an asymmetrical interaction in favour of the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Diverse effects could be produced in larvae and adults of H. axyridis after lambda-cyhalothrin exposure. Reduced predation efficacy and mobility of larva, and high acute toxicity could be mentioned as examples of these effects (Provost et al 2003(Provost et al , 2005Rodrigues 2012;Ruberson et al 2007;Torres & Ruberson 2005). The high susceptibility of H. axyridis to lambda-cyhalothrin found here is comparable to other pyrethroid insecticides, such as fenpropathrin, esfenvalerate, bifenthrin at field rates under laboratory conditions (Cho et al 1997;Galvan et al 2005Galvan et al , 2006Michaud 2002;Michaud & Grant 2003).…”
Section: Discussionmentioning
confidence: 62%
“…Diverse effects could be produced in larvae and adults of H. axyridis after lambda-cyhalothrin exposure. Reduced predation efficacy and mobility of larva, and high acute toxicity could be mentioned as examples of these effects (Provost et al 2003(Provost et al , 2005Rodrigues 2012;Ruberson et al 2007;Torres & Ruberson 2005). The high susceptibility of H. axyridis to lambda-cyhalothrin found here is comparable to other pyrethroid insecticides, such as fenpropathrin, esfenvalerate, bifenthrin at field rates under laboratory conditions (Cho et al 1997;Galvan et al 2005Galvan et al , 2006Michaud 2002;Michaud & Grant 2003).…”
Section: Discussionmentioning
confidence: 62%
“…Garcia (1979) observed that 4th instar larvae of C. sulphurea and Semidalia undecimnotata (Coleoptera: Coccinellidae) reduced the number of prey consumed after direct exposure to an identical dose of pirimicarb. Topical exposure to other pesticides such as benomyl and azadirachtin on C. maculate lengi (Roger et al 1994(Roger et al , 1995 and lambda-cyhalothrin on Harmonia axyridis (Provost et al 2005) significantly decreased the rate of aphid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of less mobile extraguild prey (phytophagous mites), to which the attacks of mirids were directed, further reduced IGP intensity (Provost et al 2005(Provost et al , 2006. Asymmetrical IGP in favour of the coccinellid was observed between Har.…”
Section: Intraguild H Emipteransmentioning
confidence: 98%